2021
DOI: 10.1101/2021.09.20.21263870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral, similar to intranasal, administration of oxytocin decreases top-down social attention

Abstract: The neuropeptide oxytocin (OXT) can modulate social cognition by facilitating attention towards social cues and may be a potential therapeutic intervention for social attention impairment in disorders such as autism. Intranasal administration of OXT is widely used to examine its functional effects in both adults and children. However, we have recently shown that administration orally as a lingual spray also modulates neural responses to emotional faces and is potentially better tolerated for therapeutic use. H… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 80 publications
(129 reference statements)
3
17
1
Order By: Relevance
“…In this paradigm, effects on volitional top-down attention are evidenced by errors and saccade latencies when subjects are required to look away from stimuli (anti-saccades) or on automatic bottom up attention when subjects are required to look toward stimuli (pro-saccades). The weaker effects of OXT on non-social top-down attention observed in previous studies (Xu et al, 2019;Zhuang et al, 2021Zhuang et al, , 2022 might have been due to greater complexity of faces compared to simple oval shapes. We therefore adapted the paradigm to include images of houses inside the oval shapes which are classically used as controls for face images (Arkush et al, 2013;Oruc et al, 2018).…”
Section: Introductioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In this paradigm, effects on volitional top-down attention are evidenced by errors and saccade latencies when subjects are required to look away from stimuli (anti-saccades) or on automatic bottom up attention when subjects are required to look toward stimuli (pro-saccades). The weaker effects of OXT on non-social top-down attention observed in previous studies (Xu et al, 2019;Zhuang et al, 2021Zhuang et al, , 2022 might have been due to greater complexity of faces compared to simple oval shapes. We therefore adapted the paradigm to include images of houses inside the oval shapes which are classically used as controls for face images (Arkush et al, 2013;Oruc et al, 2018).…”
Section: Introductioncontrasting
confidence: 56%
“…A large number of studies in humans have demonstrated that intranasal OXT enhances attention toward social relative to non-social stimuli and salient cues such as eye-gaze in both healthy (Eckstein et al, 2019;Xu et al, 2019) and autistic individuals (Andari et al, 2016;Le et al, 2022). Our previous finding that lingually administered OXT has similar effects on modulating top-down attention to social and non-social cues as intranasal administration in an anti-saccade attentional task (Zhuang et al, 2022), suggests that an oral administration route for OXT might be used therapeutically. An intranasal administration route is potentially problematic therapeutically, especially for chronic treatment, since a number of factors can influence dosing efficiency, including application technique, size of the nasal cavity and nasal congestion.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Also, experimental designs can affect statistical power of analyses. (2) Oxytocin administration route: Previous studies have shown mixed results of how oxytocin administration route affects cognitive/behavioral effects in social processing (Kou et al, 2021;Zhuang et al, 2022). (3) Non-social executive function measured as a primary vs. secondary outcome in individual studies: Whether non-social executive function was of main interest in individual studies might yield discrepant results.…”
Section: Moderator Analysesmentioning
confidence: 99%